Production and Sensory Evaluation of Novel Cheeses Made with Prebiotic Substances: Inulin and Oligofructose - Machuca, Laura Marcela (2015)
In recent years, the processing and consumption of functional foods worldwide have greatly increased. These foods benefit the body functions which improve consumers’ health and also reduce the risk factors that cause the onset of disease. Furthermore, prebiotic substances favor the multiplication of beneficial intestinal bacteria rather than harmful ones. The purpose of this study was to conduct the sensory evaluation of two functional cheeses containing inulin and oligofructose as a distinctive ingredient, including testing a cheese made with conventional ingredients, called control cheese. Affective type tests, which measured the degree of liking or disliking, were conducted using a verbal 7-point hedonic scale. According to the inclusion and exclusion criteria, 57 untrained judges were selected. This study is a quantitative, analytic and experimental-cross design. Statistical analysis of the data was performed by ANOVA with repeated measures. The results show a similar average degree of liking for the three cheeses, above 5 on the scale or “like”. By analyzing the critical level and the result of the Mauchly’s sphericity test, it is concluded that there is no statistically significant difference in the degree of liking for the three cheeses. Therefore, the addition of prebiotics to artisanal cheeses achieves to satisfy consumers and provide them benefits superior to those provided by traditional foods.